Youngsters in conflict with the law or the Law in conflict with the youngsters? Life trajectory, violence and communication means - Tedesco, Graciela (Instituto de Ciências Sociais da Universidade de Brasília, 2012)
This text analyzes the relationship between youngsters and violence through a punctual event occurred on the middle of the year 2003 that had big repercussion in the massmedia because of its clearly “news-making” character: a shocking deed (reiterated stabbing), both being young protagonists (14 and 16 years old), and the place where it happened (a school). Considering this, this text tries to deal with the trajectory of one of the youngsters who was taken to a minors reformatory institute; and in relation to the means, it considers the way through which the ideas of the “victimizer” and the “victim” need to be built based on the representations linked to traits imposed by the Justice. In this sense, the “victim” image needs to be purified and freed from all contamination; and, by its turn, the “victimizer” is associated to violence and to the uncivilized.